Analisis Dampak Nilai Taksir, Biaya dan Pelayanan terhadap Keputusan Nasabah: Studi Kasus di Pegadaian Syariah Unit Bunul Kota Malang - Jazulia, R. Rama Riyan (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
Pawn is a financing service that is now widely used to meet the needs of the community. Pawn sharia becomes one of the service products offered by Perum Pegadaian as an alternative that many people in demand. This study aims to determine the significant effect of value of assessors, costs, and services to customer decisions in Pegadaian Syariah Bunul Unit in 2017. This research is a study with non-experimental quantitative approach. Primary data is obtained through data collecting in the form of questionnaires and direct interview result from related sources. The respondents in this study ie customers who will and have used the services of pawnsharia in Pegadaian Syariah Unit Bunul Malang City as many as 83 people selected using purposive sampling technique and analyzed using SPSS 21 with multiple linear regression analysis tools. The results obtained from this study indicate that the value factor estimates, costs, services together have a significant positive effect on customer decisions in Pegadaian Syariah Bunul Unit in Malang City.